(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The article submitted materials for rare and endangered species of liverworts (Marchantiophyta, Bryobionta) of Ukraine, which are included in the official documents of different levels – in the Red Data Book of European bryophytes (1995), the Red Data Book of Ukraine (2009) Red List of European bryophytes (RLfE, 2014) or proposed for protection and are included in the Red List of bryophytes of Ukraine (Boiko, 2010). 22 species are allocated to rarity liverworts of Ukraine, which are the representatives of 16 genera 13 families of 5 orders of 3 classes – Haplomitriópsida, Marchantiópsida and Jungermanniópsida of Marchantióphyta division. Most representatives of rare species belong to the genus Scapania and family Scapaniaceae. These 22 species proposed for inclusion in the new edition of the Red Data Book of Ukraine.